STUDY OF THE COMPOSITION OF PLANTING MEDIA AND ZA FERTILIZER ON THE GROWTH AND PRODUCTION OF SAMOSIR SHALLOTS USING PVC PIPES - Edwar Pontas Harahap; Rosmayati; Nini Rahmawati (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The research was joined by Suka Raya Village, Rampah Dua Village, Pancur Batu and Deli Serdang Districts. Research launches in July 2021 and ends in November 2021. Research objective is used for ingredient resource volume as well as the development of ZA, thereby increasing Samosir's productivity and productivity. The experimental design used in this study was a factorial randomized block design with 2 factors: the first factor, namely, the composition of the planting medium with 3 treatment levels: 100% topsoil, 75% top soil: 25% cocopeat, 50 top soil soil. %: cocopeat 50%. The second factor is ZA fertilizer with 3 treatment levels: 0 g/planting hole, 1g/planting hole, and 2 g/planting hole. Parameters observed were plant length (cm), number of leaves (strands), number of tubers, tuber diameter (mm), tuber fresh weight per plant (g), tuber dry weight per plant (g), quercetin analysis (ppm). The outcomes showed that the treatment of ZA manure with a portion of 2 g/establishing opening on plant length boundaries brought about the best plant length, tuber diameter, fresh weight and dry weight of Samosir shallots, while a dose of 1 g/planting hole could increase the number of tubers and quercetin compared to the dose of 1 g/planting hole. other. The composition of the growing media, namely top soil and cocopeat, showed an increase in the growth and quality of Samosir shallots on the number of leaves and quercetin parameters. The communication between the treatment of the sythesis of the developing media and the utilization of ZA manure didn't expand the development and nature of Samosir shallots on totally noticed factors.